Evaluating Pre-Analytical Errors with Six Sigma and Pareto in A Clinical Laboratory in Lebanon - Al Akoum, Hayat; Awad, Khodor; Yassine, Haytham; Hamdan, Ali (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
The Pre-Analytical (Pre-A) phase represents up to 70% of total errors in the testing process. Six Sigma is a statistical approach used to detect and eliminate defects that impact the process. This study aimed to assess the performance of the Pre-A process according to the Six Sigma methodology at a clinical laboratory in South Lebanon. This observational study was performed over 5 months (January to May 2024). A total of 8,845 urine and stool samples, 59,497 blood samples, and 21,013 test requisition forms were screened for the most common possible Pre-A errors (hemolyzed sample, insufficient sample, missing information). Percentages of rejected samples were calculated using Microsoft Excel 2010. The Westgard online formula was used to compute Sigma as well as Six Sigma levels and defects per million opportunities for the total and each Pre-A error. A Pareto chart was also constructed based on the total number of errors and cumulative percentage. On blood sampling and test request forms, the overall rate of total critical Pre-A errors were 2.99% and 1.01%, respectively, with a Sigma level of 3.6. According to this graph, there were two most common Pre-A mistakes over the 5 months namely insufficient sample (1.18%, Sigma level: 3.8) and hemolyzed sample (0.76%, Sigma level: 4). In conclusion, the majority of the Six Sigma levels of Pre-A errors were within an acceptable range. Planned regulatory training and regular observation should be a part of the laboratory management strategy to reduce the rate of Pre-A errors and improve laboratory performance.